2014
DOI: 10.1002/jcop.21636
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and the Syndemic of Hiv‐related Health Risk Behaviors in a Diverse Sample of Transgender Women

Abstract: This study examined HIV‐related health risk behaviors–unprotected anal intercourse, alcohol intoxication, and drug use–and their association with stigma in a sample of transgender women. We conducted a cross‐sectional survey of 191 transgender women recruited through purposive sampling in San Francisco, CA. Unprotected anal intercourse, alcohol intoxication, and illicit drug use were significantly intercorrelated, suggesting the presence of a “syndemic” among these HIV‐related behavioral health risks. In multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 39 publications
5
55
0
Order By: Relevance
“…Our findings are consistent with recent research that found HIV-positive YBMSM frequently experience discriminatory treatment, ostracism, and unwanted status disclosure [51, 52]. Yet, despite its prevalence, few studies have examined stigma and its relationship to sexual, psychological, and clinical health outcomes among YBMSM across a single sample.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with recent research that found HIV-positive YBMSM frequently experience discriminatory treatment, ostracism, and unwanted status disclosure [51, 52]. Yet, despite its prevalence, few studies have examined stigma and its relationship to sexual, psychological, and clinical health outcomes among YBMSM across a single sample.…”
Section: Discussionsupporting
confidence: 91%
“…Uncovering such treatment mechanisms would suggest the most promising psychosocial processes to target in future treatment approaches. Finally, examining the efficacy of ESTEEM as specifically adapted to other diverse sexual orientation groups, including lesbian and bisexual women and transgender individuals, seeking treatment in diverse settings (e.g., community clinics) and communities (e.g., rural), would extend the promise of this intervention to the full spectrum of sexuality and gender diversity affected by minority stress processes (Lehavot & Simoni, 2011; Operario, Yang, Reisner, Iwamoto, & Nemoto, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…22 Previous research has documented frequent risk behaviors such as unprotected sex, illicit drug use, and hazardous alcohol use in samples of transgender women, 4,11 and findings have shown that stigma is associated with each of these health risk behaviors. 30 Multiple factors associated with TRD have included: low socioeconomic status, racial/ethnic status, lacking health insurance, and a history of sexual and physical violence. 19 It is unclear whether exposure to stigma has an independent association with mental health indicators among transgender women, controlling for the presence of these additional health risk factors.…”
mentioning
confidence: 99%